2020
DOI: 10.20527/jps.v7i2.7926
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Penyimpanan Obat di Gudang Farmasi RSUD Ratu Zalecha Martapura

Abstract: Penyimpanan adalah kegiatan untuk menghindari obat dari kerusakan baik fisik dan kimia serta memastikan kualitas obat tetap terjamin. Penelitian ini bertujuan untuk mengevaluasi penyimpanan obat di Instalasi Gudang Farmasi RSUD Ratu Zalecha Martapura berdasarkan indikator USAID. Penelitian bersifat deskriptif non-eksperimental dengan rancangan penelitian cross sectional dan pengambilan data dilakukan secara prospektif. Indikator yang dievaluasi yaitu tingkat akurasi persediaan obat, tingkat akurasi penempatan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…A total of 51 patients' medical records were analysed in the study. The results showed that most women and the age group over 60 years, similar to previous studies (Nori, Srikartika, and Intannia, 2015).…”
Section: Resultssupporting
confidence: 90%
“…A total of 51 patients' medical records were analysed in the study. The results showed that most women and the age group over 60 years, similar to previous studies (Nori, Srikartika, and Intannia, 2015).…”
Section: Resultssupporting
confidence: 90%
“…These results are better than the results of research at the Surakarta Regional General Hospital in 2018 which had a drug compatibility percentage of 98.44% (Desi Widyawati, 2019) and are in line with the results of research at the Sultan Agung Islamic Hospital which had a percentage result of 100% (Nuha, 2019). If there is a discrepancy or difference between the drug stock card and drug items, it can increase dead stock which can end in an increase in the number of medicines that are expired or damaged (Linda et al, 2020). The Turn Over Ratio (TOR) indicator needs to be carried out to find out how many times the capital turnover in the hospital is in one year.…”
Section: Resultsmentioning
confidence: 99%